A biotinylated ruthenium(ii) photosensitizer for tumor-targeted two-photon photodynamic therapy. Issue 73 (27th August 2019) - Li, Jia; Zeng, Leli; Xiong, Kai; Rees, Thomas W.; Jin, Chengzhi; Wu, Weijun; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract : A biotinylated ruthenium(ii ) two-photon photosensitizer was developed to selectively target cancer cells and overcome cisplatin resistance by the production of high levels of singlet oxygen. Abstract : Platinum-resistant cancer cells are sensitive to changes in the levels of reactive oxidative species (ROS). Herein, we design a biotin-modified Ru(ii ) complex as a photosensitizer (denoted as Ru-Biotin). Ru-Biotin can selectively target cancer cells and produce vast amounts of singlet oxygen under two-photon excitation at 820 nm leading to cell apoptosis. Ru-Biotin is therefore an excellent candidate to overcome platinum resistance via two-photon photodynamic therapy.